First record of Dinofelis (Felidae, Mammalia) from North Africa - (:unkn) unknown (My University, 2004)
Fragmentary dental and cranial remains from the late Pliocene of Ahl al Oughlam in Morocco are referred to Dinofelis ZDANSKY, 1924. The peculiar mastoid process, large conical upper canine and probable retention of P2 set this form aside from other species of the genus, which had not been reported from North Africa previously. However, in other features, it is closer to the Siwalik species D. cristata than to African ones.
Keywords: African Research